"Old faith is often modern heresy": Re-enchanted orthodoxy in Coleridge's "The Eolian Harp" and The Rime of the Ancient Mariner. (December 2014) - McQueen, Joseph
Charles Taylor's recent revision of secularization narratives allows for a rereading of Samuel Taylor Coleridge's "The Eolian Harp" and The Rime of the Ancient Mariner —two poems frequently construed as incompatible with Christian orthodoxy. Rather than recording a conflict between Sara Coleridge's orthodoxy and the poet's heterodoxy, "The Eolian Harp, " I claim, registers the tension between two Christianities, one secularized, the other fully enchanted. I then read the Rime not as morally and religiously unintelligible as others have, but rather as another expression of enchanted orthodoxy, one that affirms the participation of all things in the divine and that leaves room for many expressions of the numinous, not all of them benign.